Effect of temperature on microplasticity and cyclic strength of alloy 1201 - Seregin, G.V. (Проблемы прочности, 1985)
In the present work consideration is given to the effect of test temperature on microplasticity and fatigue-endurance parameters for aluminum alloy 1201. A study of the temperature dependence of fatigue strength is a very important task, since structural aluminum alloys operate over a wide temperature range.